Integration of Sustainable Accounting Principles in Local Economy-Based MSMEs in North Medan - Adi Harianto (International Journal Business, Management and Innovation Review, 2025)
The aim of this research is to explore how sustainable accounting principles are integrated into local economy-based MSMEs (Micro, Small, and Medium Enterprises) in North Medan. Sustainable accounting is increasingly recognized as a vital component for ensuring that businesses adopt environmentally responsible practices and contribute to long-term economic sustainability. This study will examine how MSMEs in North Medan implement sustainable accounting principles in their operations and the effects these practices have on their financial and environmental outcomes. Using a quantitative approach, this study will provide an in-depth and explanatory analysis of the integration process. Data will be collected through a structured survey questionnaire distributed to business owners, managers, and employees of MSMEs in North Medan. The study's population will consist of local MSMEs from various sectors in the region. A purposive sampling technique will be employed to select participants whose businesses have either adopted or are in the process of adopting sustainable accounting principles. The collected data will be analyzed using Smart PLS statistical tools to evaluate the relationships between the adoption of sustainable accounting principles and different business results, including financial performance, environmental impact, and operational efficiency. This research aims to offer a thorough understanding of the factors influencing the integration of sustainable accounting in MSMEs and its implications for local economic growth. Furthermore, the study will provide practical recommendations for MSME owners and managers on how to better incorporate sustainable accounting practices into their daily operations. The findings are anticipated to help in the development of more effective policies and strategies that encourage sustainable growth, enhance the competitiveness of MSMEs in North Medan, and offer valuable insights to policymakers and development agencies aiming to support local businesses in their shift toward more sustainable practices.